Coastal vulnerability to climate change in China's Bohai Economic Rim. (February 2021) - Zhang, Yan; Wu, Tong; Arkema, Katie K.; Han, Baolong; Lu, Fei; Ruckelshaus, Mary; Ouyang, Zhiyun
Graphical abstract: Highlights: A holistic framework was developed for assessing vulnerability to coastal hazards. Twenty percent of the coastline were categorized as having high vulnerability. The vulnerability shows spatial heterogeneity at both segment and city scales. Increased amounts of highly-threatened coasts and population were found for 2100. Abstract: Climate change and human activities exert a wide range of stressors on urban coastal areas. Synthetical assessment of coastal vulnerability is crucial for effective interventions and long-term planning. However, there have been few studies based on integrative analyses of ecological and physical characteristics and socioeconomic conditions in urban coastal areas. This study developed a holistic framework for assessing coastal vulnerability from three dimensions - biophysical exposure, sensitivity and adaptive capacity - and applied it to the coast of Bohai Economic Rim, an extensive and important development zone in China. A composite vulnerability index (CVI) was developed for every 1 km 2 segment of the total 5627 km coastline and the areas that most prone to coastal hazards were identified by mapping the distribution patterns of the CVIs in the present and under future climate change scenarios. The CVIs show a spatial heterogeneity, with higher values concentrated along the southwestern and northeastern coasts and lower values concentrated along the southern coasts. Currently, 20% of the coastlines with approximately 350, 000 people are highly vulnerable to coastal hazards. With sea-level rises under the future scenarios of the year 2100, more coastlines will be highly vulnerable, and the amount of highly-threatened population was estimated to increase by 13–24%. Among the coastal cities, Dongying was categorized as having the highest vulnerability, mainly due to poor transportation and medical services and low GDP per capita, which contribute to low adaptive capacity. Our results can benefit decision-makers by highlighting prioritized areas and identifying the most important determinants of priority, facilitating location-specific interventions for climate-change adaptation and sustainable coastal management.